Does perceived risk influence the effects of message framing? Revisiting the link between prospect theory and message framing. Issue 4 (1st October 2016) - Van 't Riet, Jonathan; Cox, Anthony D.; Cox, Dena; Zimet, Gregory D.; De Bruijn, Gert-Jan; Van den Putte, Bas; De Vries, Hein; Werrij, Marieke Q.; Ruiter, Robert A. C.
ABSTRACT: Health-promoting messages can be framed in terms of the beneficial consequences of healthy behaviour (gain-framed messages) or the detrimental consequences of unhealthy behaviour (loss-framed messages). An influential notion holds that the perceived risk associated with the recommended behaviour determines the relative persuasiveness of gain- and loss-framed messages. This 'risk-framing hypothesis', which was derived from prospect theory, has been central to health message-framing research for the better part of two decades and has enduring appeal to researchers and practitioners. It has found its way into several health communication handbooks and is communicated to the general public. The present article examines the validity of the risk-framing hypothesis anew by providing a review of the health message-framing literature. In spite of its ongoing appeal, we conclude that the hypothesis has severe theoretical flaws. In addition, we find that the empirical evidence in favour of the hypothesis is weak and inconsistent. It seems that, in applying prospect theory's tenets to a health-promotion context, some of the theory's key aspects have been lost in translation. At the close of the article, we offer a research agenda for the future, arguing that, above all, new methodology is needed to bring the message-framing literature further.